Structural basis for H3K4 trimethylation by yeast Set1/COMPASS - Takahashi, Yoh-Hei (2009)
Histone methylation on lysine 4 of histone H3 (H3K4) is a hallmark of activity of the transcribed regions on eukaryotic chromatin. H3K4 can be mono-, di- and trimethylated by Set1/COMPASS. In this review, we will discuss recent findings regarding the role of the Y/F switch by the catalytic domain of Set1 in the regulation of H3K4 methylation by Set1/COMPASS.